PENGARUH PENGETAHUAN PAJAK TERHADAP MINAT MAHASISWA BERWIRAUSAHA DENGAN SELF-EFFICACY SEBAGAI MODERASI - Yasir Hadiani; M Riduan Abdillah; Janitra Prabowo (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to analyze the effect of tax knowledge on students’ entrepreneurial interest, with self-efficacy as a moderating variable. The research is motivated by the importance of understanding taxation and self-confidence in shaping entrepreneurial behavior among accounting and taxation students. A quantitative approach was employed using primary data collected through a four-point Likert scale questionnaire. The research population consisted of active students enrolled in the Diploma III in Accounting and Bachelor of Applied Science in Tax Accounting programs at Politeknik Negeri Tanah Laut, with a total of 129 respondents who had completed entrepreneurship and taxation courses.Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results reveal that tax knowledge has a positive and significant effect on students’ entrepreneurial interest, whereas self-efficacy does not significantly moderate this relationship. The negative interaction coefficient (–0.013) indicates that at a high level of self-efficacy, the effect of tax knowledge on entrepreneurial interest tends to weaken. This suggests that students with high self-efficacy rely more on personal capability rather than cognitive aspects such as tax literacy when making entrepreneurial decisions. The findings support the Theory of Planned Behavior (Ajzen, 1991) and Self-Efficacy Theory (Bandura, 1997), emphasizing that both cognitive and psychological factors jointly influence entrepreneurial intention among accounting and taxation students.